The - Michael Howard; Wm. Roger Louis (Oxford University Press, 1998)
In this ambitious book, twenty-four of the most distinguished scholars in the world survey the momentous events and the significant themes of the twentieth century in compact, scholarly essays. The contributors tackle political issues region by region as well as non-political topics in subjects such as physics, modernism in art, international economics, and the impact of new technologies on culture. The authors trace the continuities which have persisted over the past hundred years and analyze the changes which have marked the century's progress. Early chapters take a global overview of the century as a whole, from a variety of perspectives--demographic, scientific, economic, and cultural. Further chapters chart the century's course, continent by continent and region by region, all written by acknowledged experts